Standar Kurikulum PAUD di TK Al - Kamal Laut Dendang - Nova Sari; Fadilah Sani; Adawiyah Barus; Ayu Ramadani; Fauziah Nasution (Jurnal Dirosah Islamiyah, 2023)
Early Childhood Education is a mentoring program carried out by boys and girls from birth (0 years) up to 6 years of Republic of Indonesia Law no. 20 Article I Paragraph 14 of 2003 through provisions on educational incentives to support physical and intellectual growth and development to prepare children to enter higher education. So we need educators who are reliable in curriculum development because curriculum development cannot happen haphazardly. Curriculum development that is not based on a solid foundation leads to fatal educational failure. This study aims to describe (1) the concept of developing a learning curriculum at RA Al-Kamal. (2) the concept in the learning process at RA Al-Kamal. A qualitative descriptive study of a single case study type. Researchers also collect the necessary data in the field. Data collection methods were carried out in three technical ways, namely (1) in-depth interviews, (2) observation, and (3) documentation. The process of collecting and analyzing research data is based on qualitative research data analysis steps. Conclusion This study shows the following results: 1. Summary of RA Al-Kamal, 2. Implementation of the Concept of Curriculum Development of RA Al-Kamal. Keywords: Curriculum Standards, PAUD, Curriculum Development